PENINGKATAN POWER OTOT TUNGKAI PASCA LATIHAN CIRCUIT TRAINING PADA KLUB SEPAK BOLA USIA 17 TAHUN - Wahyudi, Riki; Himawan, Agus; Fajar Hidayatullah, Fajar Hidayatullah; Haryo Mukti Widodo, Haryo Mukti Widodo (JURNAL ILMU KEOLAHRAGAAN, 2024)
In a football club, athletes must increase hard and fast kicking exercises, so that what must be considered is explosive power development exercises. One form of exercise that can improve the components of physical condition and leg muscle strength is circuit training. So this study aims to increase leg muscle power which is given the application of circuit training exercises at the Mandala FC Jaddih football club aged 17 years. The method used in this study is a quantitative approach, an experimental research type. With a sample of 15 athletes, the primary data collection process was obtained based on the results of observations in the field by conducting observations at the research location. The research design used was a one-group pretest-posttest design. The research instrument was a Standing Board Jump to measure leg muscle strength using pretest and posttest tests. From the results of the descriptive pretest test, it had a value of 2.34 and a posttest value of 3.76. From the results of the paired sample t-test, it is known that the average on the test and post-test was -1.41800 with a standard deviation of 0.58872. It produces a t-value of -9.329 and a sig (2-tiled) of 0.00. Because the sig value <5% (a) then it can be concluded that there is a difference in the pretest and posttest values. This means that circuit training has a significant effect on increasing leg muscle strength in the Mandala FC Jaddih football club aged 17 years